Az eperjesi kollégium líceumi hallgatói (1804-1850) - Dulovics, Alex (Gerundium, 2016)
THE STUDENTS OF THE COLLEGE LYCEUM AT EPERJES, 1804–1850. his study explores the history of the evangelical college of Eperjes, which was established in the second half of the 17th century and which was one of the most important institutions of higher education in Upper Hungary in the irst half of the 19th century. In the educational order of the school, which was revived in 1785. Besides classes of basic training a signiicant role was granted to the philosophical, theological, and legal training ofered in the most advanced classes. Utilizing the evidence of the data base pertaining to students who enrolled in the first half of the 19th century, the study conirms that the Eperjes school – as an institution with a higher-education quality – played a crucial role in the history of education in Upper Hungary. hroughout the irst half of the 19th century the school was capable of retaining its unique character, which permeated onto the neighbouring regions, while its educational program supplied the young generation of the evangelical nobility and of the middle class with the knowledge necessary for subsequent careers.